John Wood's Plans of Nineteenth-Century Welsh Towns. (1st December 2015) - Robson, Brian
The nineteenth-century cartographer John Wood produced detailed plans of sixteen Welsh towns which he surveyed between 1833 and 1840. They offer a fascinating portrait of the evolving urban hierarchy at a seminal stage between the market economy of the eighteenth century and the emergence of industry in the nineteenth. The detail and the accuracy of his plans provide invaluable information on the ownership of land and property, and about individual buildings and land uses in the towns. His plans should be far more widely exploited in historical urban studies.